Application of Graphene and its Derivatives in Detecting Hazardous Substances in Food: A Comprehensive Review - Pei, Jinjin; Ren, Ting; Huang, Yigang; Chen, Rui; Jin, Wengang; Shang, Shufeng; Wang, Jinze; Liu, Zhe; Liang, Yinku; Abd El-Aty, A. M. (Frontiers in Chemistry, 2022)
In this paper, we review the recent progress in the application of graphene and composite materials in food detection during the past 10 years. This mainly involves food colouring, pesticides, antibiotics, heavy metal ion residues, and other common hazards. The advantages of graphene composites in the field of electrochemical detection are described in detail, and the differences between electrochemical detection involving graphene and traditional inherent food detection are analysed and compared in depth. The results prove that electrochemical food detection based on graphene composites is more beneficial. The current defects and deficiencies in graphene composite modified electrodes development are discussed, and the application prospects and development direction of graphene in future food detection are forecasted.